Rock drawings in Badia-al sham In light of the safaitic inscriptions - رعوان شيرين (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Syria has witnessed in its ancient history flourished civilizations and stable kingdoms that have proven its distinguished position in the history of humanity, and the archaeological excavations provide us with concrete and written monuments that present Evidences of the greatness of the Syrian civilization. It has become clear that the written monuments known in our ancient Levantine languages constitute , in addition to the concrete monuments , the main and reliable scientific source for writing our ancient political and civilizational history , and from here comes the importance of research because studying these ancient languages and art forms they contain is very necessary to read and understand that history . Because Rock is an essential element on this earth, humans used it in ancient times for various uses including the use of stones to make artistic pictures by carving and clicking on them to draw human and animal figures and others called "the art of rock painting ". It represents the oldest form of artistic expression that human possesses. The inscriptions and drawings inside the caves are considered the oldest work known in humanity which revealed the mystery of many of the social customs and religious beliefs of these ancient time periods. The article will focus on these rock drawings indicating the way in which they were made , show samples of the most important of these drawings , analyze them and reveal its ambiguity through its interpretation and the access to the contents and semantic dimensions they have in order to reach important information about these time periods and the important role that these drawings played in reading safaitic human history .